Clinical Evolution and Risk Factors of Hospitalized Patients with COVID-19, Haiti, March-June 2020 - Michel, Edwige; Hetsner Denis; Roberta Bouilly; Senou Amouzou; Hebrelienne Amelus; Jean Samuel Pierre; Mauricio Cerpa; Stanley Juin; Melissa Ethéart; Nadia Phaïmyr D. Jn Charles; Gladzdin Jean- Denis; Junior Clervilus; et al. (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
In December 2019, a coronavirus epidemic emerged in China. Within months, the epidemic was considered a public health emergency of international concern. In Haiti, the first laboratory-confirmed cases of COVID-19 were reported on March 19, 2020, in a context where there was some limitations of knowledge on the modes of transmission, the severity, the clinical characteristics and the risk factors of the disease. This study has made it possible to characterize the epidemic and investigate the associations between the risk factors, co morbidities, and clinical evolution of the disease. To develop the epidemiological and clinical profile of patients with COVID-19 in Haiti, data were collected from the clinical records of patients hospitalized for COVID-19 from March 16 to June 16, 2020, in 22 healthcare facilities. Univariate, bivariate, and logistic regression model analyses were performed to describe and explore the risk factors, comorbidities, and treatments associated with patients’ clinical evolution. Statistical significance was determined using a 95% confidence interval or p-value of ?0.05. Diabetes and high blood pressure were the main comorbidities that had a statistically significant association with the severe form of the disease and the occurrence of death. The likelihood of dying increased with age, and patients in the severe form were almost four times more likely to die. The administration of ceftriaxone to patients was significantly related to recovery from the disease. Diabetes, high blood pressure, and age were the major risk factors for the severity and mortality of people infected with COVID19. Ceftriaxone administration was protective against recovery.